TAp63α induces apoptosis by activating signaling via death receptors and mitochondria - Gressner, Olav; Schilling, Tobias; Lorenz, Katja; Schulze-Schleithoff, Anna; Schulze-Bergkamen, Henning; Krammer, Peter H.; Stremmel, Wolfgang; Müller-Schilling, Martina (The EMBO journal, 2005)
TP63, an important epithelial developmental gene, has significant homology to p53. Unlike p53, the expression of p63 is regulated by two different promoters resulting in proteins with opposite functions: the full-length transcriptionally active TAp63 and the dominant-negative ?Np63. We investigated the downstream mechanisms by which TAp63α elicits apoptosis. TAp63α directly transactivates the CD95 gene via the p53 binding site in the first intron resulting in upregulation of a functional CD95 death receptor. Stimulation and blocking experiments of the CD95, TNF-R and TRAIL-R death receptor systems revealed that TAp63α can trigger expression of each of these death receptors. Furthermore, our findings demonstrate a link between TAp63α and the mitochondrial apoptosis pathway. TAp63α upregulates expression of proapoptotic Bcl-2 family members like Bax and BCL2L11 and the expression of RAD9, DAP3 and APAF1. Of clinical relevance is the fact that TAp63α is induced by many chemotherapeutic drugs and that inhibiting TAp63 function leads to chemoresistance. Thus, beyond its importance in development and differentiation, we describe an important role for TAp63α in the induction of apoptosis and chemosensitivity.